Optimalisasi Lembaga PAUD melalui Manajemen Terintegrasi: Inovasi Input, Proses, dan Output di TK Hevea - Muarif, Syamsul; Khoirumaroh, Siti; Widiatsih, Asri (STKIP PGRI SITUBONDO, 2024)
Early childhood education (ECED) is an important foundation in shaping holistic child development, including physical, cognitive, social-emotional, and spiritual aspects. The purpose of this article is to describe the management of learners' input, process and output at Hevea Kindergarten. The researcher used a qualitative approach in this study. Data were collected using interviews, observation, and documentation. Input management includes the admission program and marketing strategy. Process management includes planning, implementing and evaluating holistic approach-based learning to support children's cognitive, social, emotional and motor development. Output management focuses on evaluating educational outcomes that include skills, character and learners' readiness to continue their education to the next level. An integrated strategy, including quality input management, play-based and thematic learning processes, holistic developmental evaluation, and active collaboration with parents, demonstrates Hevea Kindergarten's commitment to producing graduates who are competitive and have superior character.